An ordinary person's guide to empire - Roy, Arundhati (Penguin, 2006)
Review: "Arundhati Roy draws the thread of empire through ostensibly disconnected arenas, highlighting in this book the parallels between the poverty draft in the United States, caste politics in India, AIDS in South Africa, reconstruction contracts in Iraq, and the perverse machinery of mass media worldwide. Above all, she issues a call to arms for people to liberate themselves from the enchantments of the self-appointed leaders of the "free world.""--BOOK JACKET